Evaluasi Peran Humanitarian Engineering dalam Rehabilitasi Infrastruktur Pascabencana di Pidie Jaya - Pitri, Deni Trianda; Muridha Hasan; Taufik; Miftahul Jannah (Seumike : Society Progress Journal, 2026)
The 6.5 magnitude earthquake that struck Pidie Jaya Regency on December 7, 2016, caused massive damage to public infrastructure and residential areas. This study aims to evaluate the implementation of Humanitarian Engineering (HE) principles in the post-disaster rehabilitation and reconstruction process. The evaluation focuses on community involvement, the effectiveness of aid distribution, and the fulfillment of construction quality standards through a socio-technical approach. Research data were gathered from official disaster authority reports, community satisfaction studies, and technical parameters of infrastructure rehabilitation. Analysis results indicate that community-based reconstruction methods have a significant positive impact on project success, with the quality factor obtaining the highest frequency index of 0.73. Nevertheless, design aspects still require adjustments to the cultural context and local needs, with an index value of 0.68. This study concludes that integrating local wisdom with earthquake-resistant engineering innovations is the key to building community resilience. Practical suggestions include strengthening system literacy for technical experts and standardizing integrated evaluation frameworks for future humanitarian projects.